Comprehensive immunophenotyping of solid tumor-infiltrating immune cells reveals the expression characteristics of LAG-3 and its ligands - Garman, Bradley; Jiang, Can; Daouti, Sherif; Kumar, Sanah; Mehta, Priyanka; Jacques, Miye K.; Menard, Laurence; Manjarrez-Orduno, Nataly; Dolfi, Sonia; Mukherjee, Piali; Rai, Sharmila Chamling; Lako, Ana; et al. (Frontiers in Immunology, 2023)
Background Immune cell expression profiling from patient samples is critical for the successful development of immuno-oncology agents and is useful to understand mechanism-of-action, to identify exploratory biomarkers predictive of response, and to guide treatment selection and combination therapy strategies. LAG-3 is an inhibitory immune checkpoint that can suppress antitumor T-cell responses and targeting LAG-3, in combination with PD-1, is a rational approach to enhance antitumor immunity that has recently demonstrated clinical success. Here, we sought to identify human immune cell subsets that express LAG-3 and its ligands, to characterize the marker expression profile of these subsets, and to investigate the potential relationship between LAG-3 expressing subsets and clinical outcomes to immuno-oncology therapies. Methods Comprehensive high-parameter immunophenotyping was performed using mass and flow cytometry of tumor-infiltrating lymphocytes (TILs) and peripheral blood mononuclear cells (PBMCs) from two independent cohorts of samples from patients with various solid tumor types. Profiling of circulating immune cells by single cell RNA-seq was conducted on samples from a clinical trial cohort of melanoma patients treated with immunotherapy. Results LAG-3 was most highly expressed by subsets of tumor-infiltrating CD8 T central memory (TCM) and effector memory (TEM) cells and was frequently co-expressed with PD-1. We determined that these PD-1+ LAG-3+ CD8 memory T cells exhibited a unique marker profile, with greater expression of activation (CD69, HLA-DR), inhibitory (TIM-3, TIGIT, CTLA-4) and stimulatory (4-1BB, ICOS) markers compared to cells that expressed only PD-1 or LAG-3, or that were negative for both checkpoints. In contrast to tumors, LAG-3 expression was more limited in circulating immune cells from healthy donors and solid tumor patients. Additionally, we found abundant expression of the LAG-3 ligands MHC-II and galectin-3 in diverse immune cell types, whereas FGL1 and LSECtin were minimally expressed by immune cells in the tumor microenvironment (TME). Lastly, we found an inverse relationship between baseline and on-treatment levels of circulating LAG3 transcript-expressing CD8 memory T cells and response to combination PD-1 and CTLA-4 blockade in a clinical trial cohort of melanoma patients profiled by scRNAseq. Conclusions These results provide insights into the nature of LAG-3- and ligand-expressing immune cells within the TME, and suggest a biological basis for informing mechanistic hypotheses, treatment selection strategies, and combination immunotherapy approaches to support continued development of dual PD-1 and LAG-3 blockade.